Taxonomic position and phylogenetic relationships of the bivalve Goniophorina Isberg, 1934, and related genera from the early Ordovician of northwestern Argentina (Ameghiniana, 2006)
Abstract. On the basis of collections from Tremadoc and Arenig successions of northwestern Argentina, the affinities of Goniophorina Isberg, 1934, are reassessed. Studied material includes ucumariids, lipanellids, Goniophorina, and other specimens for which the new genus Lossella is proposed with the new species L. juancruzi sp. nov. as type species. Goniophorina and Lossella are grouped in the new family Goniophorinidae. Synapomorphies of goniophorinids, ucumariids, and lipanellids lead to the conclusion that Goniophorina integrates a major group of edentulous bivalves, a lineage of which -the ucumariids probably gave rise to Anomalodesmata. This fauna represents a rapid, local diversification event that is part of the west-Gondwanan bivalve radiation during the early Ordovician. Resumen. POSICIÓN TAXONÓMICA Y RELACIONES FILOGENÉTICAS DEL BIVALVO GONIOPHORINA ISBERG, 1934, Y GÉNEROS RELACIONADOS DEL ORDOVÍCICO TEMPRANO, NOROESTEDE ARGENTINA. Sobre la base de colecciones del Tremadociano y Arenigiano del noroeste Argentino se discuten las afinidades de Goniophorina Isberg, 1934. El material incluye ucumariidos, lipanellidos, Goniophorina y otros ejemplares para los cuales se propone el nuevo género Lossella cuya especie tipo es L.juancruzi sp. nov. Goniophorina y Lossella se incluyen en una nueva familia, Goniophorinidae. Las sinapomorfías de goniophorinidos, ucumariidos y lipanellidos permiten concluir que Goniophorina integró un grupo de bivalvos edéntulos, de los cuales los ucumariidos probablemente dieron origen a Anomalodesmata. Esta fauna representa un rápido evento local de diversificación que forma parte de la radiación de los bivalvos en el oeste de Gondwana durante el Ordovícico temprano.